2. Surface Conditions of the Ice Sheet Traversed in 1974-1975 (II. GLACIOLOGICAL OBSERVATION IN MIZUHO PLATEAU-WEST ENDERBY LAND AREA, EAST ANTARCTICA, 1974-1975) - WATANABE, Okitsugu (National Institute of Polar Research, 1977)
P(論文) departmental bulletin paper